Modification and application of sports rehabilitation materials based on conjugated materials - Li, Han; Zhai, Xiaoyang; Yang, Zhitao; Tang, Xuan; Wang, Jingzhen; Qiu, Xuan (Frontiers in Chemistry, 2023)
Existing elastic band materials for sports rehabilitation equipment have some deficiencies in strength, flexibility and durability, and need to be further improved. Therefore, the aim of this paper is to modify elastic bands using a conjugated material, carbon nanotubes, to improve the strength, flexibility and durability of elastic bands. In this paper, conjugated carbon nanotubes were prepared, and their elastic bands were strengthened and toughened by solvent, dispersant and functionalizer respectively under tensile testing machine and scanning electron microscope. Then the application effect of elastic band modified by conjugated materials in exercise rehabilitation was analyzed experimentally. The experimental results show that the strength of the elastic bands modified with carbon nanotubes is in the optimal range for sports rehabilitation, and the elongation at break of the test elastic band toughness index was also higher than that before modification, all of which were more than 90%. The recovery time of the elastic band after modification was long; the elastic retention rate was high, and the deformation was not easy. The satisfaction rate of different grades of elastic bands after modification was particularly high, which was not less than 95%. The research and application of elastic band modification based on conjugated material carbon nanotubes is very important for training and treatment in sports rehabilitation, which can provide better support and stability.